A study on bacteria associated with three hard coral species from Ninh Thuan waters by epifluorescence and most diluted culture method - Mien, Pham Thi; Hanh, Nguyen Kim; Hieu, Nguyen Minh; Thu, Phan Minh; Du, Hoang Trung; Thi, Vo Hai; Hieu, Nguyen Trinh Duc; Dung, Le Tran; Huan, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2019)
Coral associated bacteria and their host are currently one of the interested issues for research and scientists worldwide. The densities of zooxanthellae and bacteria associated with three most prevalent species Acropora hyacinthus, Acropora muricata and Acropora robusta in Hang Rai, Ninh Thuan was evaluated over time by staining with SYBR Gold and direct counting with epifluorescence method. The most dominant bacteria were isolated by culture dependent method. The densities of zooxanthellae and bacteria ranged from 0.39–1.83×107 cell/g, and 0.83–2.52×108 cell/g, respectively. Bacterial density in the 3 months was significantly different compared to the density of the bacteria in ambient water. Total heterotrophic bacteria, comma shaped bacteria and bacillus form showed negatively correlated with pH, PO4, while zooxanthellae showed no correlation with all factors.